Effect Of Processing, (Boiling, Frying and Roasting) On The Nutrient, Antinutient And Phytochemical Composition Of Two Varieties Of Cocoyam : (Colocasia Esculenta) Colocasia antiquorum and Xantosoma sagittifolium - OLY-ALAWUBA, NKEIRUKA; Uzochukwu, Idam Prosper (Archives of Business Research, 2020)
The importance of food processing in enhancing nutrients contained in foods, cannot be overemphasized. The study evaluates the effect of different processing methods (boiling, frying and roasting), on the nutrient, antinutrient and phytochemical compositions of two varieties of cocoyam, (Colocasia antiquorum and Xanthosoma sagittifolium ). Anti-nutrients are chemical compounds evolved by plants for their defence, among other biological functions. Anti-nutrients reduce the maximum utilization of nutrients (especially proteins, vitamins and minerals), thus preventing optimal exploitation of the nutrients present in food and decreasing the nutritive value. Cocoyam (Colocasia esculenta) is a non-indigenous species, widely grown in the subtropical parts of Africa, as a traditional food crop. Cocoyam makes a significant contribution to the diet of local people in Nigeria, where it is easily available. Cocoyam varieties (X.sagittifolium and C.antiquorum), were harvested from the farm, cleaned and divided into three equal parts, (those to be boiled, fried and roasted). Thereafter, were subjected to different processing techniques before analysis. Standard assay methods were used to analyse for antinutrients, nutrients and phytochemical composition. The proximate and mineral composition of the Cocoyam varieties revealed improved values in some nutrients. Phosphorus improved (from 52.36mg/g to 65.39mg/g) Calcium (21.mg/g to 26.02mg/g), sodium (41.66 to 52.34mg/g), magnesium (11.66mg/g to 13.4mg/g), iron, (from 2.72mg/g to 5.72mg/g). The different processing methods used, especially boiling, had a diverse effect in reducing the levels of tannin, phytate, oxalate, phenols, cyanogens, saponins, flavonoids and alkaloids in relation to the other processing methods. Boiling for 30minutes was also found to be highly effective in reducing the anti-nutrient content in both varieties of cocoyam. (Tannin reduced from 0.62mg/100g to 0.15mg/100g; Phytate, from 1.83mg/100g to 0.12mg/100g and Oxalate, from 2.99mg/100g to 0.13mg/100g respectively). Alkaloid concentration decreased from 1.44mg/100g to 0.10mg/100g. Processing was effective in substantially reducing the cyanogens to low levels, from 1.44mg/100g (in raw Xanthosoma sagittifolium) to 0.07mg/100g (in boiled). The result of the study showed that some, nutrients contained in food crops, could be improved and made more available to the body, through the application of some processing methods.